2006
DOI: 10.1590/s0103-97332006000600044
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical phase transition in vibrational surface modes

Abstract: We consider the dynamical properties of a simple model of vibrational surface modes. We obtain the exact spectrum of surface excitations and discuss their dynamical features. In addition to the usually discussed localized and oscillatory regimes we also find a second phase transition where the surface mode frequency becomes purely imaginary and describes an overdamped regime. Noticeably, this transition has an exact correspondence to the oscillatory -overdamped transition of the standard oscillator with a fric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…However, the inclusion of Γ can be justified, within statistical mechanics, by including the action of a Brownian bath [41]. Recently, we obtained a simpler demonstration [42] using as environment a chain of oscillators whose N degrees of freedom are considered by taking the thermodynamic limit of N → ∞ precisely in the same way as described above in the context of the FGR. It is interesting to note that while 2ω o /Γ ≫ 1 corresponds to the standard oscillation.…”
Section: The Generalized Landauer-büttiker Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the inclusion of Γ can be justified, within statistical mechanics, by including the action of a Brownian bath [41]. Recently, we obtained a simpler demonstration [42] using as environment a chain of oscillators whose N degrees of freedom are considered by taking the thermodynamic limit of N → ∞ precisely in the same way as described above in the context of the FGR. It is interesting to note that while 2ω o /Γ ≫ 1 corresponds to the standard oscillation.…”
Section: The Generalized Landauer-büttiker Equationmentioning
confidence: 99%
“…One had to wait for the appearance of Boltzmann's statistical mechanics and the work of Smoluchowski and Einstein to have a place in the theory building (for a simple Hamiltonian model justifying friction see Ref. [42]). In any case, Aristotelian and Newtonian views, were so completely irreconcilable that Thomas Kuhn [48] concluded that they were indeed different views of Nature.…”
Section: Phase Transitions As Paradigm Shiftsmentioning
confidence: 99%
“…The intuitive idea of dynamical phase transitions is better understood by considering the classical problem of a damped harmonic oscillator in the absence of external forces. There, the oscillator presents two well defined dynamical regimes, damped and overdamped motions, which typically can be reached by moving a single parameter 34,47 . In this case, there is an analytical discontinuity in the plot of some dynamical observables, like the oscillation frequency, versus the control parameter.…”
Section: General Theorymentioning
confidence: 99%
“…In this case, there is an analytical discontinuity in the plot of some dynamical observables, like the oscillation frequency, versus the control parameter. Due to its similarity with thermodynamical phase transitions, the phenomenon is known as dynamical phase transitions 34,47 .…”
Section: General Theorymentioning
confidence: 99%
“…To compute G ± , we use a recursive decimation procedure which is an application of the real space renormalization group theory to a one-dimensional chain [20][21][22][23] . The method is conceptually simple.…”
Section: Green Functionsmentioning
confidence: 99%